2023
DOI: 10.1002/adma.202205027
|View full text |Cite
|
Sign up to set email alerts
|

Combined Vacuum Evaporation and Solution Process for High‐Efficiency Large‐Area Perovskite Solar Cells with Exceptional Reproducibility

Abstract: Organic–inorganic hybrid perovskites exhibit outstanding performances in perovskite solar cells (PSCs). However, the complex solution chemistry of perovskites precursors renders it difficult to prepare large‐area devices in a reproducible way, which is a prerequisite for the technology to make an impact beyond lab scale. Vacuum processing, instead, is an established technology for large‐scale coating of thin films. However, with respect to the hybrid perovskites it is highly challenging due to the high vapor p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 34 publications
(12 reference statements)
0
21
0
Order By: Relevance
“…The device performance of PSCs prepared by this technique is catching up and comparable with that of devices prepared using conventional toxic solution-based methods. 4 From the perspective of green synthesis of perovskites by solution deposition, water is regarded as the most promising solvent. In 2015, Wei et al first invented a low-toxicity aqueous lead nitrate ink (Pb(NO 3 ) 2 /H 2 O) to prepare MAPbI 3 PSCs via sequential deposition.…”
Section: Introductionmentioning
confidence: 99%
“…The device performance of PSCs prepared by this technique is catching up and comparable with that of devices prepared using conventional toxic solution-based methods. 4 From the perspective of green synthesis of perovskites by solution deposition, water is regarded as the most promising solvent. In 2015, Wei et al first invented a low-toxicity aqueous lead nitrate ink (Pb(NO 3 ) 2 /H 2 O) to prepare MAPbI 3 PSCs via sequential deposition.…”
Section: Introductionmentioning
confidence: 99%
“…Lead halide perovskites have been considered to be the next generation of light absorbers for photovoltaic devices as a consequence of their low cost, [1][2][3] high efficiency, [4][5][6][7] flexibility, [8][9][10] easy large-area solution processing, [11][12][13][14] etc. The high structural symmetry, high defect tolerance, and direct bandgap of lead halide perovskite crystals contribute to their excellent electrical properties, including high carrier mobility, [15,16] low Auger recombination, [17,18] and high quantum efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Tan et al reported 24.3% efficient and stable perovskite solar cells and 16 cm 2 mini-module with PCE of 20.0% using a sequential vapor-solution method in nip configuration. [37] Another combined sequential approach is the solutionvapor method, where inorganic precursors are spin-coated, followed by evaporated organic components. Wang et al have reported MA-free nip perovskite with sequential solution-vapor method, where inorganic precursors are solution deposited, following vapor-deposited FAI, and achieved over 24% of PCE and high moisture stability.…”
Section: Introductionmentioning
confidence: 99%
“…reported 24.3% efficient and stable perovskite solar cells and 16 cm 2 mini‐module with PCE of 20.0% using a sequential vapor‐solution method in nip configuration. [ 37 ] Another combined sequential approach is the solution‐vapor method, where inorganic precursors are spin‐coated, followed by evaporated organic components. Wang et al.…”
Section: Introductionmentioning
confidence: 99%